2019
DOI: 10.1101/586115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial biodiversity drives the evolution of CRISPR-based phage resistance in Pseudomonas aeruginosa

Abstract: evolution of virulence; biodiversity 19 20 21Approximately half of all bacterial species encode CRISPR-Cas adaptive immune 22 systems 1 , which provide immunological memory by inserting short DNA sequences 23 from phage and other parasitic DNA elements into CRISPR loci on the host genome 2 . 24Whereas CRISPR loci evolve rapidly in natural environments 3 , bacterial species 25 typically evolve phage resistance by the mutation or loss of phage receptors under 26 laboratory conditions 4,5 . Here, we report how th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…The magnitude of the fitness costs of CRISPR immunity and surface resistance depend on the ecological context beyond phage densities. For example, it was found that the cost of surface-based resistance relative to those of CRISPR immunity are amplified in the presence of a microbial community (Alseth et al, 2019). Moreover, these amplified costs manifested in the presence of some, but not other bacterial species.…”
Section: Fitness Costs and Benefits Of Crispr Immunitymentioning
confidence: 99%
“…The magnitude of the fitness costs of CRISPR immunity and surface resistance depend on the ecological context beyond phage densities. For example, it was found that the cost of surface-based resistance relative to those of CRISPR immunity are amplified in the presence of a microbial community (Alseth et al, 2019). Moreover, these amplified costs manifested in the presence of some, but not other bacterial species.…”
Section: Fitness Costs and Benefits Of Crispr Immunitymentioning
confidence: 99%
“…Coevolution under different environmental pressures may shift dynamics between 'arms race' and 'fluctuating' with implications for phage resistance (41,42). Introducing other bacterial species that capture the multispecies nature of many infections may also change how resistance develops (43), shifting selection from the receptor target to other resistance mechanisms such as CRISPR-cas (43).…”
Section: Discussionmentioning
confidence: 99%
“…Such costs (of bacterial defence) are of particular interest in the context of phage therapy since they could reduce the ability of the bacterial pathogen to respond to demanding environments, or to actively modify their environments. Recent work on community dynamics of phage therapy employing a virulent lysogenic phage in vitro has shown that the form of resistance could change depending on the local bacterial community [76].We discuss the impacts of phage steering on community dynamics in Box 3.…”
Section: Box 2 Alternative Resistance Mechanisms and Indirect Targetsmentioning
confidence: 99%
“…Chronic infections are often polymicrobial in nature and are receiving increasing attention [81]. Phage have been shown to affect the types of mutation that occur when bacteria compete in complex communities [76]. Surface factors that mediate interactions between the different species or with the environment are potential targets for phage steering.…”
Section: Box 3 What Is a Good Target For Phage Steering?mentioning
confidence: 99%